Mitragyna speciosa may be useful as an opioid alternative for severe pain relief. More research is required - Cock, I.E. (Pharmacognosy Communications)
Mitragyna speciosa Korth. (commonly known as kratom or ketum) is an evergreen tree in the coffee family (Rubiaceae). It is native to the Indo- china and Malaysia botanical regions of Southeast Asia. It is indigenous to Indonesia, Malaysia, Myanmar, Papua New Guinea and Thailand and is a part of the traditional pharmacopeias of all of the regions in which it occurs. It is used traditionally to relieve pain and fatigue, as well as cough and diarrhoea. Kratom has potent pain killing effects which begin within 5-10 min of consumption and last for up to 5 hours.1 A number of pharmacologically compounds have been identified in kratom leaves, including mitragynine, mitragynine pseudoindoxyl, mitraphylline, 7-hydroxymitragynine, paynantheine, speciogynine, rhynchophylline, raubasine and corynantheidine.2-6 Interestingly, whilst they have simi- lar indications as the opoids for pain relief, kratom and the opoids have pharmacologically and biochemically distinct actions.7 Thus, kratom is also useful to aid in opoid withdrawal.